Quilombola ethnobotany: a case study in a community of slave descendants from the center of the Cerrado biome (Research, Society and Development, 2020)
Current Quilombola communities are remnants of Brazilian slave communities. The community of Cedro, municipality of Mineiros – GO, uses botanical resources from the Cerrado biome to compose herb-based remedies, that constitute an important source of income for residents. The aim of this work was to evaluate this slave tradition considering i. the pattern of plant use; ii. the relationship between origin and compound taxonomic richness; and iii. the consensus on plant use X pharmacological actions proposed in local medicine. Data were obtained using free listing and snowball techniques, semistructured interviews and guided tours. The results indicated that the community presents a wide pattern of species use; in 380 ethno-references, 166 species were mentioned. The families Fabaceae, Asteraceae and Lamiaceae were richer in species and ethno-references; most of the plants are native and were collected in backyards or a typical Cerrado. Infused and decocted teas were the most diverse preparation methods (H' = 2.6201), and they were primarily used to address diseases of the digestive and metabolic system. The species with higher use values (UV) were Cymbopogon citratus, Citrus limon, Hymenaea courbaril, Dysphania ambrosioides and Baccharis trimera (UV>1). This work constitutes an important survey about the ethnobotanical knowledge of descendants of slaves and demonstrates the importance of the resources of the Cerrado biome for therapy in Quilombola communities that developed in the center of this biome.